A robotic vehicle for disabled children. - Ceres, R.
One of the most frequent effects of physical disability is reduced or impaired mobility. There are a number of technical aids for all the cases of physical impairment but none of the systems described in the literature address the particular problems of children affected by neuromotor disorders accompanied by mental retardation. The following addresses the development of the PALMA [(plataforma de apoyo ludico a la movilidad alternative) (assistive platform for alternative mobility)] system as a tool to assist the mobility of children affected by cerebral palsy. PALMA is specifically adapted to a personalized and early cognitive development of children affected by severe neuromotor problems. The rehabilitation process based on PALMA has an impact on the interaction between children and environment, on their motor dexterity, and on decision-making ability.
Keywords: PALMA; Assistive platform for alternative mobility; Cerebral palsy; Cognitive development; Decision-making ability; Disabled children; Impaired mobility; Mental retardation; Motor dexterity; Neuromotor disorders; Physical disability; Plataforma de apoyo ludico a la movilidad alternativa; Rehabilitation tool; Robotic vehicle